1999
DOI: 10.1038/10223
|View full text |Cite
|
Sign up to set email alerts
|

Real-time control of a robot arm using simultaneously recorded neurons in the motor cortex

Abstract: To determine whether simultaneously recorded motor cortex neurons can be used for real-time device control, rats were trained to position a robot arm to obtain water by pressing a lever. Mathematical transformations, including neural networks, converted multineuron signals into 'neuronal population functions' that accurately predicted lever trajectory. Next, these functions were electronically converted into real-time signals for robot arm control. After switching to this 'neurorobotic' mode, 4 of 6 animals (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
482
0
19

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 990 publications
(519 citation statements)
references
References 32 publications
10
482
0
19
Order By: Relevance
“…The brain-machine interface field has been dominated by applications in which neural signals recorded from motor or premotor areas are used to predict kinematic signals: the position of a cursor on a computer screen (Serruya et al 2002, Taylor et al 2002, Santhanam et al 2006, Kennedy and Bakay 1998, Wolpaw and McFarland 2004 or the endpoint of a robotic limb (Serruya et al 2002, Chapin et al 1999, Taylor et al 2003, Carmena et al 2003. We have demonstrated that similar techniques can be used to predict the activity of individual muscles of the arm and hand.…”
Section: Prediction Of Kinetic Signalsmentioning
confidence: 99%
“…The brain-machine interface field has been dominated by applications in which neural signals recorded from motor or premotor areas are used to predict kinematic signals: the position of a cursor on a computer screen (Serruya et al 2002, Taylor et al 2002, Santhanam et al 2006, Kennedy and Bakay 1998, Wolpaw and McFarland 2004 or the endpoint of a robotic limb (Serruya et al 2002, Chapin et al 1999, Taylor et al 2003, Carmena et al 2003. We have demonstrated that similar techniques can be used to predict the activity of individual muscles of the arm and hand.…”
Section: Prediction Of Kinetic Signalsmentioning
confidence: 99%
“…Whenever the user induces a voluntary modification of these patterns, the BCI system is able to detect it and to translate it into an action that reflects the user's intent. Several animal and some human studies have shown the possibility to use electrical brain activity recorded within the brain to directly control the movement of robots or prosthetic devices in real time using microelectrodes implanted within the brain [6] [7][8] [9] [10]. Other BCI systems depend on brain activity recorded non-invasively from the surface of the scalp using electroencephalography (EEG).…”
Section: Introductionmentioning
confidence: 99%
“…More recent work reports similar memory activity in parietal cortex before reaches (Snyder et al, 1997) and grasps (Sakata et al, 1995) relating parietal cortex to movement plans in general. There is great interest in helping paralyzed patients by using cortical SU activity to control a prosthesis (Kennedy and Bakay, 1998;Chapin et al, 1999) and the relation of parietal SU activity to movement planning makes it a potentially useful signal (Shenoy et al, 1999). However, the difficulty of isolating SU activity with cortical implants has presented a major hurdle to the development of a neural prosthesis.…”
mentioning
confidence: 99%